Market Mechanisms and Market Distortions in the Perspective of Islamic Economics - Dewi, Riska; Kurniasih, Dewi (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Previous studies on market mechanisms and market distortions according to Islamic economics in imperfect markets on Monopoly and Oligopoly markets were the subject of this study. This research uses descriptive qualitative methods; the authors use descriptional data such as words or a library survey of the research. The results show that the Islamic economy wants market mechanisms free of government intervention. According to Islamic economics, market mechanisms and pricing must be regulated to maintain market balance and economic justice, taking into account the interests of each party